KONSTITUSIONALISME BERNEGARA DAN KEPATUHAN TERHADAP PUTUSAN MAHKAMAH KONSTITUSI - Arrasuli, Beni Kharisma (Ensiklopedia Sosial Review, 2019)
The establishment of the constitution guarantor institute is aimed at making the constitutional rights of every citizen or state institution not easily harmed by power through legislation, so that in the amendment to the 1945 Constitution of the Republic of Indonesia the Constitutional Court is present as an institution serving as the guarantor of the constitution. the number of legal norms that exist in a country and many institutions that are authorized to form them can be ascertained that the contradictions from the existing norms will require a dispute breaker institution, the character of the Constitutional Court's decision is final and binding to differentiate with other judicial institutions, as well as the decision of the Court bind the whole party without exception, not only the parties disputed but also public member, it is only the issue that arises into a problem after the Constitutional Court decides a case of reviewing laws that are considered contrary to the constitution, it should be the legislative body in this case such as the People's Representative Council and the President or other relevant state institutions obey the decision and implement it. However, because the Constitutional Court does not have an executive tool for the decision, it is still a great homework by this country, the ethics of state that should be prioritized by the parties in complying with the Court's ruling. This is study that will be the author’s explain in this paper.